ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) MEMBAYAR PAJAK PENGHASILAN DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL MODERATING - Imas Fatimah (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2019)
The purpose of this study was to examine whether Knowledge and Understanding of Taxation Regulations, Good Perceptions of the Effectiveness of the Taxation System, Level of Trustworthiness in the Legal System and Government affect the willingness of MSMEs to pay income tax with Economic Growth as a moderating variable.The population in this study were MSME entrepreneurs in the City of South Tangerang in the period 2017. The data processing was carried out with the help of the SPSS 22.0 program and WarpPLS 5.0.The results showed that the Knowledge and Understanding of Taxation Regulations, Good Perceptions of the Effectiveness of the Taxation System and the Level of Trust in the Legal and Government System have a significant effect on the willingness of MSMEs to pay income tax.Economic growth does not strengthen the influence of the interaction of Knowledge and Understanding of Tax Regulations and the Level of Trustworthiness in the Law and Government Systems on the willingness of MSMEs to pay income tax. Economic growth reinforces the interaction of Good Perception on the Effectiveness of the Taxation System on the willingness of MSMEs to pay income tax.